Applying game-based learning at the South African Military Academy: an experimental study. (12th April 2019) - Dreyer, Adriaan M.F.; Dodd, Nicole; Dalton, Wayne O.
The contemporary military environment is characterised by new technologies, advances in computer usage, and a generation of young students who have the expectation that the use of technology within education will increase over the next few years. Research suggests games within education to be a feasible solution for positively supplementing traditional teaching practices, making learning more interactive and enjoyable. Despite this, there is mixed empirical support for the successful use thereof. The aim of this study was to investigate if using Game-Based Learning (GBL) compared to traditional teaching methods when teaching JavaScript to undergraduate Computer Information Systems (CIS) students at the South African Military Academy (MA), would result in statistically significant higher learning gains. A research experiment was conducted to investigate this aim using a sample of 47 (n = 47) residential students. Participants were tested on their JavaScript knowledge using a pre- and post-test experimental design. The variables and results in learning gains from the two experimental groupings showed no significant statistical difference, but significant learning gains resulted when compared to the control group.